Optimising the measurement of bruises in children across conventional and cross polarized images using segmentation analysis techniques in Image J, Photoshop and circle diameter measurements. (February 2018) - Harris, C.; Alcock, A.; Trefan, L.; Nuttall, D.; Evans, S.T.; Maguire, S.; Kemp, A.M.
Abstract: Background: Bruising is a common abusive injury in children, and it is standard practice to image and measure them, yet there is no current standard for measuring bruise size consistently. We aim to identify the optimal method of measuring photographic images of bruises, including computerised measurement techniques. Methods: 24 children aged <11 years (mean age of 6.9, range 2.5–10 years) with a bruise were recruited from the community. Demographics and bruise details were recorded. Each bruise was measured in vivo using a paper measuring tape. Standardised conventional and cross polarized digital images were obtained. The diameter of bruise images were measured by three computer aided measurement techniques: Image J (segmentation with Simple Interactive Object Extraction ( maximum Feret diameter ), 'Circular Selection Tool' ( Circle diameter ), & the Photoshop 'ruler' software ( Photoshop diameter )). Inter and intra-observer effects were determined by two individuals repeating 11 electronic measurements, and relevant Intraclass Correlation Coefficient's (ICC's) were used to establish reliability. Spearman's rank correlation was used to compare in vivo with computerised measurements; a comparison of measurement techniques across imaging modalities was conducted using Kolmogorov-Smirnov tests. Significance was set at p < 0.05 for all tests. Results: Images were available for 38 bruises in vivo, with 48 bruises visible on cross polarized imaging and 46 on conventional imaging (some bruises interpreted as being single in vivo appeared to be multiple in digital images). Correlation coefficients were >0.5 for all techniques, with maximum Feret diameter and maximum Photoshop diameter on conventional images having the strongest correlation with in vivo measurements. There were significant differences between in vivo and computer-aided measurements, but none between different computer-aided measurement techniques. Overall, computer aided measurements appeared larger than in vivo. Inter- and intra-observer agreement was high for all maximum diameter measurements (ICC's > 0.7). Conclusions: Whilst there are minimal differences between measurements of images obtained, the most consistent results were obtained when conventional images, segmented by Image J Software, were measured with a Feret diameter. This is therefore proposed as a standard for future research, and forensic practice, with the proviso that all computer aided measurements appear larger than in vivo. Highlights: Precise measurement of bruises is integral to child abuse evaluations. Conventional and Cross polarized images of childhood bruises were taken. Maximum Feret, circle and Photoshop were compared to paper tape measurements. Highest precision achieved using the maximum Feret diameter on a conventional image.